2017
DOI: 10.1186/s13287-016-0462-5
|View full text |Cite
|
Sign up to set email alerts
|

Culture supernatant of adipose stem cells can ameliorate allergic airway inflammation via recruitment of CD4+CD25+Foxp3 T cells

Abstract: BackgroundIn a previous study, we demonstrated that intravenous administration of adipose tissue stem cells (ASCs) could significantly reduce allergic symptoms and suppress eosinophilic inflammation.MethodsTo evaluate the secretome of ASCs, we administrated culture supernatant of ASCs (ASC sup, which contains the ASC secretome) and uncultured fresh medium (con sup) into a mouse model of allergic airway inflammation. Subsequently we observed the mice for signs of inflammation and investigated Th1-, Th2-, and Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…ASCs: adipose stem cells; Bex2: brainexpressed X-linked 2; CON: control; EV: extracellular vesicle; Fpr1: formyl peptide receptor 1; Igfbp6: insulin-like growth factor binding protein 6; OVA: ovalbumin; PON1: paraoxonase 1; Scgb1c1: secretoglobin family 1C member 1. Stem Cells International cytokine production and induction of Treg expansion [19,22]. Furthermore, ASC-derived EVs have been shown to reduce static lung elastance and collagen fiber deposition in lung parenchyma and airways in experimental allergic asthma [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ASCs: adipose stem cells; Bex2: brainexpressed X-linked 2; CON: control; EV: extracellular vesicle; Fpr1: formyl peptide receptor 1; Igfbp6: insulin-like growth factor binding protein 6; OVA: ovalbumin; PON1: paraoxonase 1; Scgb1c1: secretoglobin family 1C member 1. Stem Cells International cytokine production and induction of Treg expansion [19,22]. Furthermore, ASC-derived EVs have been shown to reduce static lung elastance and collagen fiber deposition in lung parenchyma and airways in experimental allergic asthma [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, MSCs have several drawbacks including immune rejection, risk of aneuploidy, difficulty of handling, and tumorigenicity. Previous studies have shown that ASC-derived secretome-containing EVs, even without ASCs, ameliorate allergic airway inflammation through the suppression of Th2 cytokine production and induction of Treg expansion [ 19 , 22 ]. Furthermore, ASC-derived EVs have been shown to reduce static lung elastance and collagen fiber deposition in lung parenchyma and airways in experimental allergic asthma [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of Tregs is a pivotal mechanism by MSCs to exert immunosuppressive functions. Mechanisms involved in Treg induction by MSCs have been dug deeply [33,34]. The study by Akiyama et al showed that intravenous transfer of mouse bone marrow MSCs to naive mice induced T cell apoptosis in peripheral blood and bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms of these effects remain to be clarified. Several studies have observed anti-inflammation effects after the transplantation of adipose-derived stem cells (ASCs) in vitro and in vivo, with increased interleukin (IL)-10 and suppression of the NFκB signaling pathway [ 10 , 11 , 12 , 13 , 14 , 15 ]. Two of these studies also demonstrated anti-neuroinflammation effects [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%